USE OF REMOTE SENSING AND GEOGRAPHIC INFORMATION SYSTEMS FOR FOREST RESOURCE BALANCE MAPPING IN LEMBAH GUMANTI DISTRICT, SOLOK DISTRICT - sausaen, laura ovia; Syarief, Azhari; Iswandi U, Iswandi U; Putri, Sri Kandi (Remote Sensing Technology Study Program, 2024)
The forest resources balance sheet prepared for the implementation of law no. 41 of 1999 ratified article 13 paragraph (4), in the technical process of implementation it always refers to the decision of the Minister of Forestry no. 6444/kpts-ll/1999 regarding instructions for preparing forest resource balance sheets. The forest resource balance sheet is information that describes forest resource reserves, loss and use of forest resources so that at a certain time the trend of surplus or deficit compared to the previous period can be seen. Law. 41 of 1999, article 13 paragraph 4. Remote sensing offers great potential for the development of methods for calculating the balance of forest resources and changes in the forest sector and geographic information systems (SIG) which are used to provide digital form and analysis of the earth's geographic surface so as to form precise and accurate spatial information. This research uses quantitative analysis. This research aims to determine changes in forestry stocks in the Gumanti Valley district, and knowledge about forest balance in the Gumanti Valley region. The results of research based on data show that around -12,708 ha of land in the form of secondary forest has experienced a reduction or deficit in area. Apart from that, other land that has experienced a reduction in area is primary forest. Meanwhile, the land that has experienced the most significant increase in area is in the form of fields covering an area of ​​+13,239 ha from 2017 to 2023.